Public policies for Brazilian family farming in a semiarid climate: from combat to coexistence - Campelo, Daniel Alves (Revista Brasileira de Pós-Graduação, 2014)
The work presents public policies aimed at farmer families, especially those who live in semiarid regions, with the general objective of presenting the ideologies of draught-fighting public policies at the beginning of the 20th century, and comparing them with policies made for coexistence with the semiarid climate, which brings a new strategic configuration for the sustainability of local development. We therefore presented the importance of public policies for small-scale agriculture and the promotion of sustainable development against the backdrop of the droughts cycle in the period between 1900 and 1970, as well as paradigm shifts in family farming production models, starting with conventional models, through the period that became known as the green revolution, and up to agroecology.